2021
DOI: 10.3389/fpls.2020.618873
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Alleviate Hypoxia Stress by Improving Enzymatic and Non-enzymatic Antioxidants and Regulating Nutrient Uptake in Muscadine Grape (Muscadinia rotundifolia Michx.)

Abstract: Flooding induces low oxygen (hypoxia) stress to plants, and this scenario is mounting due to hurricanes followed by heavy rains, especially in subtropical regions. Hypoxia stress results in the reduction of green pigments, gas exchange (stomatal conductance and internal CO2 concentration), and photosynthetic activity in the plant leaves. In addition, hypoxia stress causes oxidative damage by accelerating lipid peroxidation due to the hyperproduction of reactive oxygen species (ROS) in leaf and root tissues. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 67 publications
(57 reference statements)
0
11
0
Order By: Relevance
“… 79 Barickman et al 35 also found that the gas exchange parameters of the leaves decreased, and photosynthetic activity was damaged in cucumber under flooding stress. In a study by Zafar et al, 2 flooding stress also reduced the gas exchange parameters ( G s and C i ) and photosynthetic activity of muscadine grape ( Muscadinia rotundifolia Michx.) leaves.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“… 79 Barickman et al 35 also found that the gas exchange parameters of the leaves decreased, and photosynthetic activity was damaged in cucumber under flooding stress. In a study by Zafar et al, 2 flooding stress also reduced the gas exchange parameters ( G s and C i ) and photosynthetic activity of muscadine grape ( Muscadinia rotundifolia Michx.) leaves.…”
Section: Discussionmentioning
confidence: 89%
“… 69 70 Similar to most abiotic stresses, flooding stress also reduces the photosynthetic capacity of plants, primarily in the reduction of photochemical activity and ability to assimilate carbon ability. 2 33 Chlorophyll fluorescence technology has become one of the most powerful and widely used techniques used to understand the photosynthetic processes and thus, serve as a reliable indicator of stress in plants. 71 Therefore, this study used this technique to analyze the effects of flooding stress on the activities of PSII and PSI in mulberry leaves.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations